Minimizing Task Offloading Delay in NOMA-MEC Wireless Systems - Irum, Tayyaba; Usman Ejaz, Muhammad; Elkashlan, Maged (2022 4th Global Power, Energy and Communication Conference (GPECOM), 2022)
This paper investigates a non-orthogonal multiple access (NOMA) based mobile edge computing (MEC) system with multiple users. We aim to optimize the offloading delay of multiple users subject to transmit power and offloading data rate constraints in NOMA enabled MEC system. We first converted the non-convex formulated minimization problem into a convex domain by proposing the convex approximation method and then the low complexity binary search algorithm is proposed to find the global optimal solution. Simulations are performed, showing that the proposed NOMA scheme outperforms the orthogonal multiple access (OMA) access in terms of time taken by task offloading. Motivated by the better performance of NOMA over OMA, the proposed NOMA scheme can be recommended for the future wireless communication system with massive connectivity and intensive computational demand.